The Influence of Organizational Commitment and Leadership Style Factors through Knowledge Sharing on The Performance of Employees of The State Civil Apparatus in The Investment and One-Door Integrated Services Office in East Luwu Regency - Amiruddin Amiruddin; Mahlia Muis; Wahda Rasyid (Magister Management, Hasanuddin University, 2020)
Improving the quality of government services in the era of globalization and digitalization is a demand for the State Civil Apparatus (SCA) to improve its performance. Employee performance is influenced by several factors such as organizational commitment, leadership style, and knowledge sharing. However, the phenomenon that exists in the field today is that the efforts made in building a sense of organization commitment, leadership style, and knowledge sharing of each SCA have not been maximized. This also happened at the Investment and One-Door Integrated Services Office (IODISO) of East Luwu Regency. For this reason, this research is expected to be able to provide solutions to the relevant agencies in improving employee performance. The three factors that have been mentioned are then measured using a questionnaire with question items in the form of a Likert scale that is submitted to each respondent. So the data obtained in the form of quantitative data. This data is then analyzed using path analysis. The analysis showed that organizational commitment and leadership style had a direct positive influence on knowledge sharing significantly. Then organizational commitment, leadership style, and knowledge sharing also have a positive direct effect on employee performance. Whereas organizational commitment and leadership style have an indirect positive influence through knowledge sharing on employee performance. This organizational commitment, leadership style, and knowledge sharing contributed to an influence of 92.1% on employee performance.